Pengembangan E-Modul Pemrograman Berbasis Computational Thinking Mata Pelajaran Informatika Bagi Kelas X SMK - Gulo, Delfi Ardius; Kurniadi, Denny (Jurnal Vokasi Teknik Informatika, 2024)
Facing the challenges of the Industrial Revolution 4.0 requires mastery of digital literacy, one of which is the ability to use computers effectively. In Indonesia, students can learn how computers operate through Informatics subjects, particularly in Programming Algorithms. However, learning Programming Algorithms is not sufficient if it is limited to the classroom using textbooks as the main learning resource. The high potential of mobile phone usage among the Indonesian population, as indicated by data from GoodStats and the 2022 Indonesian Telecommunication Statistics, can be utilized to integrate this technology into learning. The type of research used in this study is Research and Development (R&D), employing the ADDIE model. This article proposes the development of a self-directed digital learning material (E-Module) in the form of a smartphone application based on the Android platform. The E-Module presents interactive content such as videos, images, and animations to enhance student engagement by integrating the principles of Computational Thinking (CT), which are essential for developing problem-solving and critical thinking skills. Validation results from subject matter experts show that the E-Module achieved a feasibility score of 94.5%. This assessment confirms that the E-Module is highly suitable for student trials, with content aligned to the curriculum, communicative language, systematic presentation, and appealing graphic design. The E-Module is expected to be effective in improving students' understanding, motivation, and critical thinking skills in Programming Algorithms.